Second transplantation after kidney graft loss in primary hyperoxaluria type 2: a pedigree study and mutation analysis - Yushi Peng; Yingchun Zheng; Fu Xiong; Mingming Zhang; Yuchen Wang; Jia Luo; Wenli Zeng; Jialiang Hui; Wenfeng Deng; Jian Xu; Yun Miao; Renfei Xia; et al. (Renal Failure)
Background Primary hyperoxaluria type 2 (PH2) is a rare disorder caused by GRHPR mutations. Research on the mutation spectrum and pedigree of PH2 helps in comprehending its pathogenesis and clinical outcomes, guiding clinical diagnosis and treatment.Methods We report a case of PH2 with a three-generational pedigree. The GRHPR genotypes of the family members were confirmed by Sanger sequencing. Urine and blood samples were collected for biochemical analysis. Computational analysis was performed to assess the pathogenicity of the mutations. Cellular experiments based on site-directed mutagenesis were conducted to confirm the effect of mutations on GRHPR expression, activity, and subcellular localization.Results The proband underwent her first kidney transplantation in 2015, and experienced recurrent urinary tract infections and urolithiasis postoperatively. Graft failure occurred in 2018. Whole exome sequencing identified compound heterozygous GRHPR mutations p.G160E/p.P203Rfs*7. The patient underwent a second kidney transplantation in 2019 and maintained good graft function with urine dilution measures. Notably, her brother and sister carried the same mutations; however, only the proband progressed to renal failure. Computational analysis suggested that p.G160E reduced the affinity of GRHPR for coenzymes. Cellular experiments indicated that p.G160E reduced GRHPR activity (p < 0.001), whereas p.P203Rfs*7 not only suppressed expression (p < 0.001) and reduced activity (p < 0.001), but also facilitated protein aggregation. Based on our results, the variant p.G160E was classified as ‘pathogenic’ according to ACMG guidelines.Conclusions Our findings suggest that treatment strategies for the long-term prevention of oxalate nephropathy should be developed for patients with PH2 receiving isolated kidney transplantation. Moreover, the pathogenicity of the compound heterozygous GRHPR mutations p.G160E/p.P203Rfs*7 was also validated.